'Gunboats of soft power': Boris on Africa and post-Brexit 'Global Britain'. Issue 4 (4th July 2017) - Połońska-Kimunguyi, Eva; Kimunguyi, Patrick
Abstract: As Britain prepares to leave the European Union after the popular vote of June 2016, the government is embarking on the revision of foreign policy. Boris Johnson, or 'just Boris', has been entrusted with forging the new 'Global Britain' for the post-Brexit era and reinventing British economy around new relationships. Boris has a track record of misrepresenting and offending foreign peoples, leaders and countries. This article assesses the prospects for Africa in Johnson's vision for 'Global Britain' as presented in his foreign policy speeches. The paper unpacks Johnson's discursive construction of 'Africa' and inserts it into a broader historical and political context of British relations with Africa. It argues that, by constructing Africa as a 'problem' and offering liberal values as a condition for development, Johnson is continuing British imperial and post-colonial discourses of 'developing' or 'civilizing' Africa. In the post-Brexit world of a changing global balance of power, democratic conditionality serves to sustain and reproduce British forms of power and policies.